Nutritional Status and the Affecting Factors in the Elderly in Gonbad Kavus, Iran - Navisa Seyed Ghasemi; Mina Dazi; Bahareh Nikrad; Hasan khorsha; Amrolah Sharifi; Mohammad Reza Honarvar (Golestan University of Medical Sciences, 2021)
Background: The elderly population is projected to increase in Iran and the world. A large number of chronic diseases observed in the elderly could be prevented or treated by improving their lifestyle, including nutrition. The present study aimed to determine nutritional status and the affecting factors in the elderly in Gonbad Kavus, Iran.  Methods: This descriptive-analytical study was performed on 139 elderlies aged more than 60 years who resided in Gonbad (northeast of Iran) in 2013. The subjects were selected via two-stage cluster sampling, and each health center was considered as a cluster. Data were collected using a demographic questionnaire and mini nutritional assessment (MNA) questionnaire. Moreover, anthropometric indices (e.g., weight and height) were measured using a fabric meter, stadiometer, and Seca scale. Data was analyzed in SPSS version 11.5 using Chi-square and ordinal logistic regression model.  Results: In total, 36% of the elderlies had a normal nutritional status, whereas 59% and 5% were at the risk of malnutrition and malnourished, respectively. Among the subgroups, the female elderlies (78.6%) and single participants (87.1%) were at the risk of malnutrition or malnourished. Gender was the only independent variable affecting malnutrition. In addition, malnutritional status and marital status were the only variables affecting the body mass index even in the presence of other variables.  Conclusion: Based on the nutritional assessment of the elderly, special attention must be paid to elderly women with lower education levels and financial dependence. It is also recommended that periodic assessments be carried out in the elderly population using the MNA questionnaire.Background: The elderly population is projected to increase in Iran and the world. A large number of chronic diseases observed in the elderly could be prevented or treated by improving their lifestyle, including nutrition. The present study aimed to determine nutritional status and the affecting factors in the elderly in Gonbad Kavus, Iran.  Methods: This descriptive-analytical study was performed on 139 elderlies aged more than 60 years who resided in Gonbad (northeast of Iran) in 2013. The subjects were selected via two-stage cluster sampling, and each health center was considered as a cluster. Data were collected using a demographic questionnaire and mini nutritional assessment (MNA) questionnaire. Moreover, anthropometric indices (e.g., weight and height) were measured using a fabric meter, stadiometer, and Seca scale. Data was analyzed in SPSS version 11.5 using Chi-square and ordinal logistic regression model.  Results: In total, 36% of the elderlies had a normal nutritional status, whereas 59% and 5% were at the risk of malnutrition and malnourished, respectively. Among the subgroups, the female elderlies (78.6%) and single participants (87.1%) were at the risk of malnutrition or malnourished. Gender was the only independent variable affecting malnutrition. In addition, malnutritional status and marital status were the only variables affecting the body mass index even in the presence of other variables.  Conclusion: Based on the nutritional assessment of the elderly, special attention must be paid to elderly women with lower education levels and financial dependence. It is also recommended that periodic assessments be carried out in the elderly population using the MNA questionnaire.